2018
DOI: 10.1155/2018/4735234
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s Decision to Disclose the Use of Traditional and Complementary Medicine to Medical Doctor: A Descriptive Phenomenology Study

Abstract: Nondisclosure of traditional and complementary medicine (T&CM) use may cause individual to be at risk of undue harm. This study aimed to explore patient's experience and views on their decision to disclose the use of T&CM to the doctor. An exploratory qualitative study using in-depth interview involving 10 primary care clinics attendees in Kuching was conducted. The results indicated that disclosure of T&CM use will motivate them to get information, increase doctor's awareness, and get support from family and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 40 publications
3
33
0
1
Order By: Relevance
“…However, it is important to note that the use of CAM products might be associated with hazardous health risks related to their adverse effects, improper dosage or quality of the products (eg, contamination, misidentification or lack of standardisation) 9. These risks could be amplified due to the low rate of disclosure to healthcare providers for fear of their disapproval, disinterest or inability to help 10–13. Such lack of professional supervision may further expose the consumer to various risks, including adverse reactions or interactions with conventional drugs 6 14 15…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to note that the use of CAM products might be associated with hazardous health risks related to their adverse effects, improper dosage or quality of the products (eg, contamination, misidentification or lack of standardisation) 9. These risks could be amplified due to the low rate of disclosure to healthcare providers for fear of their disapproval, disinterest or inability to help 10–13. Such lack of professional supervision may further expose the consumer to various risks, including adverse reactions or interactions with conventional drugs 6 14 15…”
Section: Introductionmentioning
confidence: 99%
“…This may be justified by Fear of negative response from doctors. In addition to doctor's communication skills and providing enough time for the patient [23]. A study conducted in USA showed another perspective which is; most of the physicians were not comfortable in counseling their patients about CAM treatments [24].…”
Section: Resultsmentioning
confidence: 99%
“…These include the small number of responders; the majority of whom were females may be because women are more open and receptive to a health concern and tend to share problems [23,27]. Future studies should focus on testing a larger sample, of equal males and females percentages in order to avoid gender bias.…”
Section: Potential Limitations To This Studymentioning
confidence: 99%
“… 94 Patients should be encouraged to discuss the use of T&CM and conventional medications with both T&CM practitioners and conventional medicine clinicians during their consultation. 95 …”
Section: People-centered Policies For Integrating Tandcm Into Health Symentioning
confidence: 99%